Failure Analysis of Graphite Epoxy Composite Plate Under Transverse Sinusoidal Load - Fazli Adull Manan, Nor; Firdaus Mohd Jam, Mohammad; Kumar Sahu, Shishir; Mahmud, Jamaluddin (International Journal of Engineering and Technology, 2018)
Composite material become interest on various applications in wide industry globally. The selection of composite material due to its versatile properties for instance high specific strength. Besides, the properties of composite material also tailorable for various application including automotive, aerospace and marine industry. The objective of this study is to perform the failure analysis of composite material under transverse sinusoidal load. Both failure criteria, Maximum Stress and Tsai-Wu Failure Criteria that provided in ANSYS used to carry out the analysis. Various aspect ratios will be used which are 5, 10, 20, 50 and 100 to perform the analysis with different thickness of laminate. Next, the boundary condition of the plate was set to simply and clamp supported. The finite element analysis of graphite/epoxy laminate with layup of (0/90/90/0) performed to determine the failure loads (First Ply Failure, FPF and Last Ply Failure, LPF loads). The un-normalized load obtained from the analysis is converted to normalized load using equation given. Finally, normalized load is plotted against aspect ratio for both failure criteria and boundary conditions.Â Â